(untitled) (Italian Review of Legal History, 2023)
Teodolfo Mertel, jurist and historian, statesman and cardinal (Allumiere, 1806-ivi, 1899), dedicated an unpublished essay to the municipal statutes. Found in the Vatican Apostolic Archives, the essay was intended to be an introduction to the printed edition of the entire official collection of the statutes adopted by the communities subjected to the Holy See from the Middle Ages. The collection, preserved in Rome, was significantly enriched and systematised on the initiative of Mertel in his capacity as Minister of the Interior of the Papal States, a position held from 1853 to 1858. Mertel frames the statutory source in the context of the municipal affair, distinguishes the various types of statutes and examines the contents with examples taken from the statutory specimens in the collection. The stated objective is the historiographical re-evaluation of the statutory source. Mertel aims at something higher than the simple historical-erudite revitalisation of the local statutory source: he considers the statutes as bearers of a deep layer of principles that give rise to modern legal systems and political institutions. In the regulation and institutional organisation of medieval municipalities, he finds the roots of some constitutional notions and techniques – for example, the representative principle, the division or balance of powers – at the heart of the theoretical reflection and European juridical-political debate of the early nineteenth century. Mertel’s essay fits entirely into the context of the broad and lively debate of the nineteenth century on the role of medieval municipal systems in the process – and model – of incivilimento.